prove that sinx-cosx+1/sinx+cosx-1=1/secx-tanx
Answers
Answered by
13
GIVEN :
Prove that
TO PROVE :
The following equation
SOLUTION :
Given that
We have to prove that the equation is true.
Now taking the LHS ![\frac{sinx-cosx+1}{sinx+cosx-1} \frac{sinx-cosx+1}{sinx+cosx-1}](https://tex.z-dn.net/?f=%5Cfrac%7Bsinx-cosx%2B1%7D%7Bsinx%2Bcosx-1%7D)
Let S=sinx and C=cosx
Multiply and divide by (S-C)-1 we get,
By using the Algebraic identity :
By using the trignometric identity :
where sinx=C and cosx=C
∴ ![\frac{sinx-cosx+1}{sinx+cosx-1}=\frac{cosx}{1-sinx}\hfill (1) \frac{sinx-cosx+1}{sinx+cosx-1}=\frac{cosx}{1-sinx}\hfill (1)](https://tex.z-dn.net/?f=%5Cfrac%7Bsinx-cosx%2B1%7D%7Bsinx%2Bcosx-1%7D%3D%5Cfrac%7Bcosx%7D%7B1-sinx%7D%5Chfill+%281%29)
Now taking the RHS ![\frac{1}{secx-tanx} \frac{1}{secx-tanx}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bsecx-tanx%7D)
By using the trignometric identities
i) and
ii)
∴ ![\frac{1}{secx-tanx}=\frac{cosx}{1-sinx}\hfill (2) \frac{1}{secx-tanx}=\frac{cosx}{1-sinx}\hfill (2)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bsecx-tanx%7D%3D%5Cfrac%7Bcosx%7D%7B1-sinx%7D%5Chfill+%282%29)
Comparing the equations (1) and (2) we get,
⇒ (1) = (2)
∴ LHS=RHS
∴
Hence proved.
Similar questions